Integrated silicon-metal systems at the nanoscale : applications in photonics, quantum computing, networking, and internet /: applications in photonics, quantum computing, networking, and internet. (2023) - Nayfeh, Munir H (Munir Hasan); Nayfeh, Ammar
No abstract available